Antimicrobial susceptibility, virulence gene and pulsed-field gel electrophoresis profiles of Salmonella enterica serovar Typhimurium recovered from retail raw chickens, China. (February 2017) - Li, Keting; Ye, Shuyao; Alali, Walid Q.; Wang, Yin; Wang, Xin; Xia, Xiaodong; Yang, Baowei
Abstract: A total of 138 Salmonella enterica serovar Typhimurium isolates recovered from retail raw chickens in seven provinces of China from 2007 to 2012 were characterized for antimicrobial susceptibility, genotype and presence of virulence genes. Resistance was most frequently detected to sulfisoxazole (90.6%), tetracycline (73.2%), nalidixic acid (65.9%), ceftiofur (59.4%), ampicillin (54.3%) and kanamycin (34.8%). Resistance to cefoxitin (6.5%), amikacin (5.8%) and ceftriaxone (3.6%) was less frequently detected. One hundred and thirty seven (99.3%) isolates were resistant to at least one antibiotic, and 82 (59.4%) to more than five antibiotics. Pulsed-field gel electrophoresis (PFGE) subtyping generated 66 PFGE patterns and 12 clusters. Isolates with similar PFGE patterns in the same cluster were all resistant to similar categories and numbers of antibiotics and harbored similar virulence genes. Among 30 virulence genes we screened for, the top five genes were pag K (82.6%), sod C1 (66.7%), sii E (58.7%), pef A (58.7%) and mar T (50.7%). All isolates were identified harboring at least one virulence gene, 80 (58.0%) and 16 (11.6%) were simultaneously positive for at least nine and seventeen virulence genes, respectively. Twenty four (17.4%) isolates harbored at least ten virulence genes and exhibited resistance to at least ten antibiotics. Our results revealed that S. Typhimurium isolates in retail raw chickens were not only genotype multiform, but majority of them were multidrug resistant and co-carried multiple virulence genes, which may pose great potential hazard to public health. Highlights: Multidrug resistance was commonly identified in 138 S. Typhimurium isolates. pag K, sod C1 and sii E were frequently detected among 30 virulence genes surveyed. Isolates with similar PFGE pattern cocarried similar virulence genes. Multidrug resistant isolates simultaneously co-carried multiple virulence genes.